The Consequences of the TCJA's International Provisions: Lessons from Existing Research - Dhammika Dharmapala (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper discusses the potential consequences of the international tax provisions of the recent Tax Cut and Jobs Act (TCJA), drawing on existing research. The TCJA's dividend exemption provision is expected to eliminate distortions to the amount and timing of dividend repatriations. However, the efficiency gains from increased repatriations – which are primarily expected to increase shareholder payout – are likely to be modest. The paper uses the observed behavior of firms during the repatriation tax holiday implemented in 2005 to infer the relative magnitudes of the burdens created by the repatriation tax under the old (pre-TCJA) regime and by the TCJA's new “Global Intangible Low-Taxed Income” (GILTI) tax. It concludes that the TCJA increases the tax burden on US residence for many, and perhaps most, US MNCs. The paper also argues that the GILTI and “Foreign-Derived Intangible Income” (FDII) provisions are likely to create substantial distortions to the ownership of assets, both in the US and around the world. Overall, the scholarly evidence implies that the international provisions of the TCJA can reasonably be expected to create potentially large efficiency losses.
Keywords: H25; 330; international taxation; tax reform; tax cut and jobs act; GILTI; FDII